1989
DOI: 10.3109/01485018908986792
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin and Calcitonin in Human Semen

Abstract: The levels of beta-endorphin (beta-E) and calcitonin were estimated in 36 samples of seminal plasma from semen of normospermic, oligozoospermic, and azoospermic origins and in pools of isolated sperm. The mean levels in plasma calculated for all samples examined were 192 +/- 224 pg/ml for beta-E and 754 +/- 397 pg/ml for calcitonin. The amounts in sperm were as follows: for beta-E in pools with sperm counts of 0.1-10 x 10(6)/ml, 157.2 +/- 99.7 pg/10(8) and 27.9 +/- 23.6 pg/ml protein; in pools of greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The present data confirm the presence of POMCderived peptides in the testis and genital tract of stallion, whose function could be linked to sperm motility, as suggested by Singer et al (1989), Fraioli et al (1984 and Graczykowski et al (1990). Such effects seem to be not dependent on the peptide locally synthesized, since the molecular biology approach, here applied, is consistent with the presence of POMC transcript found in the pituitary only.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present data confirm the presence of POMCderived peptides in the testis and genital tract of stallion, whose function could be linked to sperm motility, as suggested by Singer et al (1989), Fraioli et al (1984 and Graczykowski et al (1990). Such effects seem to be not dependent on the peptide locally synthesized, since the molecular biology approach, here applied, is consistent with the presence of POMC transcript found in the pituitary only.…”
Section: Discussionsupporting
confidence: 88%
“…Semen quality and stallion reproductive behavior are reduced in winter time, being seasonaly largely influenced by photoperiod (Nishikawa, 1959;Picket et al, 1970;Magistrini et al, 1987;Clay and Clay, 1992;Ginther, 1992), and primarily conveyed to the brain and pineal gland through a complex neural pathway that effects the hypothalamus-pituitary-gonadal axis (Sharp et al, 1993;Sharp, 1999); seasonal changes of spermatogenesis, together with the regulation of stallion sperm maturation, having been also investigated at cellular level (Sutovsky et al, 2003). Moreover, Aurich et al (1994) demonstrated the involvement of endogenous opioids in reproductive functions in the horse, showing opioid regulation of LH and PRL secretion, and the role of endorphins being emphasized in the process of sperm mobility, through their effects on calcium transport (Singer et al, 1989). The occurrence of b-EP in spermatozoa and in the seminal plasma of stallion were previously demonstrated using immunocytochemical and biochemical methods (Carnevali et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These high levels suggest an existing source of seminal plasma. Although calcitonin level was 44 times higher in seminal plasma than that in blood plasma, there was no correlation between blood and seminal plasma calcitonin levels in terms of sperm motility [1,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Fraioli et al [3] demonstrate that beta-endorphin and calcitonin might act as potent motility inhibitors, with certain concentrations of beta-endorphin sperms being affected. Singer et al [20] suggest that the high cellular beta-endorphin and calcitonin levels would be involved in the process of motility through their effect on calcium transport. The estimation of beta-endorphin does not precisely correlate with the male reproductive function in humans as it comes from different sources, for example, the pituitary, which yields the major source in peripheral circulation, the hypothalamus, the gastrointestinal tract, the adrenal gland, the pancreas, the lymphocytes, the erythrocytes leucocytes and the reproductive system.…”
Section: Tel: +86-21-5492-2824; Fax: +86-21-5492-2825; Shanghai Chinamentioning
confidence: 99%